Chainsaw location finding based on travelling of sound wave in air and ground - Phumpichet Jubjainai; Sittichai Pathomwong; Poom Siripujaka; Na Chiengmai; Anek Chaiboot; Paramote Wardkein (My University, 2020)
Abstract Deforestation is a major problem in the world because it affects to temperature and increasing carbon dioxide. In this research, it is therefore proposed that the sound signal inspection of chainsaw which take place from deforest activity and localize the position of deforesting by using the sound signal detection of chainsaw that travels in two mediums are in the air and soil and find the time difference which two waves in both medium travel to the observer or the detector. The correlation operation is used to determine the time difference to calculate the distance between the sound source and the observer and find the direction of the sound source by rotating the microphone to get the most magnitude of sound and take the direction and distance to specify the location of the loggers. Which the proposed system is low complexity and energy-saving and can move easily. From the system test, it was found that the accuracy was 95%.
Keywords: Observer (physics); SIGNAL (programming language); Position (finance); Remote Sensing and LiDAR Applications